2020
DOI: 10.3389/fcimb.2020.00483
|View full text |Cite
|
Sign up to set email alerts
|

A Novel sRNA in Shigella flexneri That Regulates Tolerance and Virulence Under Hyperosmotic Pressure

Abstract: Regulation of the environmental stress response and virulence of Shigella flexneri may involve multiple signaling pathways; however, these mechanisms are not well-defined. In bacteria, small regulatory RNAs (sRNAs) regulate bacterial growth, metabolism, virulence, and environmental stress response. Therefore, identifying novel functional sRNAs in S. flexneri could help elucidate pathogenic adaptations to host micro-environmental stresses and associated virulence. The aim of this study was to confirm the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, deletion of all these sRNAs had no significant effect on the growth pattern of 05ZYH33 ( Figure 2(c)) , indicating the deletion of these sRNAs may not influence bacterial growth under normal culture conditions. Previous studies showed that deletion of certain sRNA does not affect the bacterial growth under normal culture conditions but they are implicated in pathogenesis [ 21 ]. Next, a BALB/c mouse model was used to evaluate the effect of sRNA76, sRNA23 and sRNA24 deletion on the pathogenicity of S. suis 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, deletion of all these sRNAs had no significant effect on the growth pattern of 05ZYH33 ( Figure 2(c)) , indicating the deletion of these sRNAs may not influence bacterial growth under normal culture conditions. Previous studies showed that deletion of certain sRNA does not affect the bacterial growth under normal culture conditions but they are implicated in pathogenesis [ 21 ]. Next, a BALB/c mouse model was used to evaluate the effect of sRNA76, sRNA23 and sRNA24 deletion on the pathogenicity of S. suis 2.…”
Section: Resultsmentioning
confidence: 99%
“…The link between OMV fusion and repression of VirF remains uncharacterized; however, it is possible that the fusion of lipids contained in B. thetaiotaomicron OMVs into the membrane of S. flexneri triggers stress responses. Virulence gene expression in S. flexneri and other enteric pathogens is known to be closely intertwined with bacterial stress responses ( 61 66 ). B. thetaiotaomicron OMVs fusing to S. flexneri may activate envelope stress response two-component systems, and then these directly or indirectly transduce the signal of B. thetaiotaomicron OMV fusion from the outer membrane of S. flexneri to VirF.…”
Section: Discussionmentioning
confidence: 99%
“…The link between OMV fusion and repression of VirF remains uncharacterized; however, it is possible that the fusion of lipids contained in Bt OMVs into the membrane of S. flexneri triggers stress responses. Virulence gene expression in S. flexneri and other enteric pathogens is known to be closely intertwined with bacterial stress responses (6166). Bt OMVs fusing to S. flexneri may activate envelope stress response two-component systems, and then these directly or indirectly transduce the signal of Bt OMV fusion from the outer membrane of S. flexneri to VirF.…”
Section: Discussionmentioning
confidence: 99%